Answer:
see below
Explanation:
1^2+2^2+3^2+...+n^2=n(n+1)(2n+1)/6
Step1
Verify it for n=1
1^2= 1(1+1)(2*1+1)/6= 1*2*3/6= 6/6=1 - correct
Step2
Assume it is correct for n=k
1^2+2^2+3+2+...+k^2= k(k+1)(2k+1)/6
Step3
Prove it is correct for n= k+1
1^2+2^2+3^2+...+(k+1)^2= (k+1)(k+2)(2k+2+1)/6
prove the above for k+1
1^2+2^2+3^2+...+k^2+(k+1)^2= k(k+1)(2k+1)/6 + (k+1)^2=
= 1/6(k(k+1)(2k+1)+6(k+1)^2)= 1/6((k+1)(k(2k+1)+6(k+1))=
=1/6((k+1)(2k²+k+6k+6))= 1/6(k+1)(2k²+4k+3k+6))=
= 1/6(k+1)(2k(k+2)+3(k+2))=
=1/6(k+1)(k+2)(2k+3)
Proved for n= k+1 that:
the sum of squares of (k+1) terms equal to (k+1)(k+2)(2k+3)/6